Ovarian superstimulatory response and embryo production in mares treated with equine pituitary extract twice daily - Alvarenga, Marco Antonio [UNESP]; McCue, P. M.; Bruemmer, J.; Neto, JRN; Squires, E. L. (Elsevier B.V., 2001)
Equine pituitary extract (EPE), has been reported to induce multiple ovulation in mares, however ovulation rates are poor in comparison to those obtained in other species. Attempts to improve the effectiveness of EPE for induction of superovulation in cyclic mares has focused on daily frequency of EPE treatment. Two experiments were performed to compare the ovarian response of cyclic mares given EPE once or twice-daily. Mares were assigned to one of two treatment groups 6 to 8 days after ovulation: prostaglandin was given once and EPE (25 mg) was given once daily (Group 1) or twice daily (Group 2). In Experiment 1, more (P < 0.05) follicles <greater than or equal to>35 mm were detected in mares treated with EPE twice daily (6.1 +/- 3.1) than in mares treated once a daily (2.0 +/- 0.6). In a second experiment, the embryo recovery rates of mares given the two EPE protocols used in Experiment 1 were compared. The number of ovulations per mare was higher (P < 0.05) for mares treated twice-daily (7.1 +/- 5.1, range 3 to 18) than for mares treated once daily (2.4 +/- 1.8, range 1 to 6). The number of embryos produced per mare was higher (P < 0.05) in mares in Group 2 (3.5) than in Group 1 (1.6).Although it is not clear whether the increased ovulation rate is due specifically to dose or frequency, twice-daily administration of a high dose of EPE significantly improved follicular development, ovulation and embryo recovery over the standard treatment of once-daily injection. (C) 2001 by Elsevier B.V.
Keywords: superovulation; mare; equine pituitary extract; embryo recovery